Pola Penyelenggaraan Pendidikan dan Pelatihan Di Balai Diklat Keuangan Kota Malang - Edi Widianto (Faculty of Education Universitas Negeri Malang, 2018)
Abstract: Balai Diklat Keuangan (BDK) Malang is one of the educational institutions and training under the auspices of the Ministry of Finance of the Republic of Indonesia. Implementation of the training organized by the institution are not necessarily held on the decision of the head of the hall. But through the needs assessment phase to various institutions under the finance ministry to put forward a work program or training program during a budget year. The learning process in training were emphasized on the development of skills of trainees. This study aims to determine the pattern of providing education and training in BDK Malang. This study uses a qualitative approach with case study design. The location of this research at BDK Malang. The results of research showed that: (1) BDK Malang has a characteristic which is supported by training human resources to work in accordance with the SOP that is on it. Given these institutions work in accordance with the BDK Malang can not develop the kind of training independently which is open to the public. This means that this institution only organizes training for human resources in the Ministry of Finance; (2) the process of training in the management and development of BDK Malang arranged in two stages that complement each other; and (3) educational and training organized by BDK Malang has a quite different pattern of educational and training that exist elsewhere. Abstrak: Balai Diklat Keuangan (BDK) Malang merupakan salah satu lembaga pendidikan dan pelatihan yang bernaung dibawah Kementerian Keuangan Republik Indonesia. Pelaksanaan diklat yang diselenggarakan oleh pihak lembaga tidak serta merta diselenggarakan atas keputusan kepala balai. Melainkan melalui tahap need assesment (penilaian kebutuhan) kepada berbagai lembaga dibawah kementerian keuangan untuk diajukan sebagai program kerja atau program diklat selama satu tahun anggaran. Proses pembelajaran pada diklat lebih di tekankan pada pengembangan skill peserta pelatihan. Penelitian ini bertujuan untuk mengetahui pola penyelenggaraan pendidikan dan pelatihan di Balai Diklat Keuangan Kota Malang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis rancangan studi kasus. Lokasi penelitian ini di Balai Diklat Keuangan Kota Malang. Hasil penelitian menunjukkan bahwa: (1) BDK Kota Malang memiliki karakteristik pelatihan yang ditunjang oleh sumberdaya manusia yang bekerja sesuai dengan SOP yang ada di atasnya. Mengingat lembaga ini bekerja sesuai dengan BDK Kota Malang tidak bisa mengembangkan jenis mata diklat secara mandiri yang bersifat terbuka untuk umum. Artinya lembaga ini hanya menyelenggarakan diklat untuk SDM di kawasan Kemenkeu; (2) proses pengelolaan dan pengembangan Diklat di BDK Kota Malang diatur dalam dua tahapan yang saling melengkapi; dan (3) diklat-diklat yang diselenggarakan oleh BDK Kota Malang memiliki pola yang cukup berbeda dengan diklat-diklat yang ada di tempat lain.